Współczesne trendy w rozwoju architektury systemów informowania kierownictwa - Zygała, Ryszard (Trends in Developing Executive Information System Architectures, 2007)
Today, the executive information systems are one of the more important components of the IT infrastructure in business. EIS now are computerized information systems designed to directly support senior executives. They are developed in order to provide fast and easy access to information from a variety of sources, both internal and external to the business. The main goal of the paper is to present the contemporary EIS architecture trends.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 98-110